Complex absorbing potential based equation-of-motion coupled cluster method for the potential energy curve of CO2- anion - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav; Bartlett, Rodney J. (Journal of Chemical Physics, 2014)
The equation-of-motion coupled cluster method employing the complex absorbing potential has been used to investigate the low energy electron scattering by CO2. We have studied the potential energy curve for the (2)Pi(u) resonance states of CO2- upon bending as well as symmetric and asymmetric stretching of the molecule. Specifically, we have stretched the C-O bond length from 1.1 angstrom to 1.5 angstrom and the bending angles are changed between 180 degrees and 132 degrees. Upon bending, the low energy (2)Pi(u) resonance state is split into two components, i.e., (2)A(1), B-2(1) due to the Renner-Teller effect, which behave differently as the molecule is bent. (c) 2014 AIP Publishing LLC.